Edwardsiella tarda-Induced Inhibition of Apoptosis: A Strategy for Intracellular Survival - Zhou, Ze-jun; Sun, Li (Frontiers in Cellular and Infection Microbiology, 2016)
Edwardsiella tarda is a Gram-negative bacterial pathogen that can infect a wide range of freshwater and marine fish. One salient feature of E. tarda is the ability to survive and replicate in various host cells. In this study, we observed that E. tarda replicated robustly in the zebrafish cell line ZF4, and that E. tarda-infected cells exhibited no detectable signs of apoptosis. Global transcriptome analysis and quantitative real-time RT-PCR revealed that E. tarda infection generally significantly downregulated pro-apoptotic genes and upregulated anti-apoptotic genes. To investigate the role of apoptosis in E. tarda infection, two upregulated anti-apoptotic genes (Fech and Prx3) and two downregulated pro-apoptotic genes (Brms1a and Ivns1a) were overexpressed in zebrafish. Subsequent infection study showed that Fech and Prx3 overexpression significantly promoted E. tarda dissemination in and colonization of fish tissues, while Brms1a and Ivns1a overexpression significantly reduced E. tarda dissemination and colonization. Consistently, when Fech and Prx3 were knocked down in zebrafish, E. tarda infection was significantly inhibited, whereas Brms1a and Ivns1a knockdown significantly enhanced E. tarda infection. These results indicate for the first time that E. tarda prevents apoptosis in teleost as a strategy for intracellular survival, and that some putative apoptotic genes of teleost function in the apoptosis pathway probably in a manner similar to that in mammalian systems.